Signaling and transport processes related to the carnivorous lifestyle of plants living on nutrient-poor soil. Issue 4 (22nd June 2021) - Böhm, Jennifer; Scherzer, Sönke
Abstract: In Eukaryotes, long-distance and rapid signal transmission is required in order to be able to react fast and flexibly to external stimuli. This long-distance signal transmission cannot take place by diffusion of signal molecules from the site of perception to the target tissue, as their speed is insufficient. Therefore, for adequate stimulus transmission, plants as well as animals make use of electrical signal transmission, as this can quickly cover long distances. This update summarises the most important advances in plant electrical signal transduction with a focus on the carnivorous Venus flytrap. It highlights the different types of electrical signals, examines their underlying ion fluxes and summarises the carnivorous processes downstream of the electrical signals.